2023
DOI: 10.1186/s12889-023-15290-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between socioeconomic status and risk of obesity and overweight among Chinese children and adolescents

Abstract: Background In China, the threat of obesity and overweight in children and adolescents is developing quickly. It may be possible to lower the risk of obesity and overweight in children and adolescents by understanding the factors that drive these conditions. Therefore, this study aimed to investigate the association between SES and risk of obesity and overweight among children and adolesecnts in China’s provinces of Jiangsu, Anhui, Zhejiang, and Shanghai. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…Other similar studies conducted in China have largely focused on school-aged children in specific provinces or regions [ 28 , 40 , 44 , 54 ], but this study extends its scope encompassing preschool-aged children, thus, covering the entire crucial growth period of early childhood in China. This study departs from other studies that have employed limited criteria for assessing overweight and relying solely on children's BMI, which lacks adjustments for age and gender, hence, resulting in inaccurate overweight or obesity evaluations [ 27 , 39 , 47 ]. Primarily, this study captures the protective effect of mothers with only junior high school education against childhood overweight under 5.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Other similar studies conducted in China have largely focused on school-aged children in specific provinces or regions [ 28 , 40 , 44 , 54 ], but this study extends its scope encompassing preschool-aged children, thus, covering the entire crucial growth period of early childhood in China. This study departs from other studies that have employed limited criteria for assessing overweight and relying solely on children's BMI, which lacks adjustments for age and gender, hence, resulting in inaccurate overweight or obesity evaluations [ 27 , 39 , 47 ]. Primarily, this study captures the protective effect of mothers with only junior high school education against childhood overweight under 5.…”
Section: Discussionmentioning
confidence: 74%
“…On contrary, a survey conducted on childhood obesity among children aged 9–17 in coastal provinces of the Yangtze River Delta region, uncovered a positive relationship between higher socioeconomic status and overweight in girls. This effect was particularly pronounced when mothers had completed high school education or higher [ 27 ]. An investigation into obesity inequality among children aged 9–12 in the northeastern region found that at both extremes of socioeconomic status, children from the lowest-educated parents and the highest-educated parents experienced a lower risk of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Y Ke et al found similar result identical to our study. The observed higher prevalence rates of obese children in upper class may be because of sedentary lifestyles, altered eating patterns and increased sugar and fat content of their diet Poor Physical life style was more often present in overweight and obese children as compared to not overweight children 23 . Findings of the study revealed that age group between 9-11, 8.1% obese and 16.3% were overweight children and age group between 12-14, 7.1% obese and 18.2% were overweight.…”
Section: Discussionmentioning
confidence: 95%
“…This revelation may have public health implications. When studying the health habits of people with high socio-economic status, it is essential to consider how educational attainment may influence the prevalence of overweight or obesity (18). Longitudinal studies are needed to improve the effectiveness of interventions and better understand the causal relationship between socioeconomic status and BMI.…”
Section: Discussionmentioning
confidence: 99%